Early Career Stars of the Decade - Charles Rosenblatt; Helen F. Gleeson (Crystals, 2021)
The field of liquid crystals is constantly reinventing itself, evolving from measurements of elastic constants and devices such as the simple nematic twist cell in the 1970s to topological defects, nanoparticle inclusions, and smart sensors today [...]